Examination of Millennial MSMEs' Decision-Making Factors Mentored by Rumah BUMN Sidoarjo on Obtaining Halal Certification - Muhammad Syarofi (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Halal certification has become a strategic instrument for Micro, Small, and Medium Enterprises (MSMEs) to enhance consumer trust, expand market access, and ensure the sustainable development of the national halal sector. Nevertheless, the level of halal certification ownership among MSMEs, particularly those managed by the millennial generation, remains relatively limited and exhibits diverse responses to existing policies. This study aims to analyze the determinants influencing the decision of millennial MSMEs fostered by Rumah BUMN Sidoarjo to obtain halal certification. The research adopts a quantitative approach with an explanatory research design. Data were collected through a structured questionnaire survey administered to the entire population of 25 millennial MSMEs under the guidance of Rumah BUMN Sidoarjo, and the data were analyzed using multiple linear regression techniques. The variables examined include MSME halal awareness, regulatory processes, trust and reputation, economic factors, religiosity, and halal literacy. The findings reveal that MSME halal awareness, regulatory processes, trust and reputation, religiosity, and halal literacy have a positive and significant effect on the decision of millennial MSMEs to obtain halal certification. In contrast, economic factors do not show a significant influence, indicating that cost considerations are not the primary determinant within the context of MSMEs assisted by Rumah BUMN Sidoarjo. These findings suggest that halal certification decisions are driven more by value awareness, institutional support, and halal-related knowledge than by short-term economic considerations. Theoretically, this study enriches the halal business literature through a multidimensional analytical approach, while practically it provides a foundation for policy formulation aimed at strengthening halal literacy, simplifying regulatory procedures, and enhancing sustainable MSME assistance programs.